(untitled) (Texas Journal of Engineering and Technology, 2022)
The article considered an analysis of existing methods for increasing durability (silent block and piston coupling of a shock absorber), as well as other vehicle suspension components. We substantiated the possibility of restoring the working capacity of the silent block and piston couplings of shock absorbers by replacing worn parts with an innovative repair kit, respectively, with conical and cylindrical spring inserts and developing a mathematical model